Frakturen der lateralen Tibiavorderkante : Der vierte Knöchel - Rammelt, Stefan; Bartoníček, Jan; Neumann, Annika Pauline; Kroker, Livia (Der Unfallchirurg, 2021)
The anterolateral tibial rim with the anterior tibial tubercle (Tubercule de Tillaux-Chaput) serves as an insertion site of the anterior inferior tibiofibular ligament (AITFL). It can also be termed the anterior malleolus or fourth malleolus. Fractures of the anterolateral tibial rim typically result from an external rotation or abduction mechanism of the talus within the ankle mortise. They are frequently overlooked in plain radiographs. Computed tomography (CT) is needed for an exact visualization of the fracture anatomy and treatment planning. A total of three main types can be differentiated: (1) extra-articular avulsion fracture of the AITFL, (2) fracture of the anterolateral distal tibia with involvement of the joint and tibial incisura and (3) impaction fracture of the anterolateral tibial plafond. Surgical fixation of displaced anterolateral distal tibial fractures aims at bone-to-bone stabilization of the anterior syndesmosis, restoration of the tibial incisura for the distal fibula and joint surface. Displaced extra-articular avulsion fractures (type 1) are fixed with a suture anchor or transosseal suture. Larger fragments involving the tibial incisura and plafond (type 2) are mostly fixed with screws. Impression fractures of the anterolateral tibial plafond (type 3) necessitate elevation with restoration of the joint surface, bone grafting of the impaction zone as needed and anterior buttress plating. Only a few studies have reported the treatment results of anterolateral tibial rim fractures in adults. Conservative treatment of dislocated fragments reportedly leads to non-union and malposition of the distal fibula with incongruence of the ankle mortise requiring revision. Impaction fractures (type 3) can lead to secondary avascular necrosis of the anterolateral tibial plafond.
Keywords: dospělí; Ankle Fractures; fibula; Ankle joint; Adult; Anterior malleolus; ligamentum laterale articulationis talocruralis; Internal fixation; Tillaux fracture; fraktury tibie; lidé; Tibia; Tibial Fractures; Fibula; Tibiofibular syndesmosis; tibie; vnitřní fixace fraktury; Lateral Ligament, Ankle; Fracture Fixation, Internal; fraktury kotníku; Humans